2019
DOI: 10.1080/10371656.2019.1658285
|View full text |Cite
|
Sign up to set email alerts
|

Testing indicators of resilience for rural communities

Abstract: The resilience of rural communitiestheir ability to adapt to change over timeis a concern in itself and for its effects on the agricultural sector. The present pilot study investigated the possibility of using official statistics for the purpose of measuring resilience, and in particular tested the possibility of identifying resilience thresholds for the indicators. The study used community workshops to investigate the drivers of self-reported resilience among residents of four rural communities in New Zealand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Meanwhile, Rela et al [1] tested the dimensions of community action; collective orderliness; and community, social and environmental adaptation. In the context of community resilience in rural areas, Payne et al [38] and William Kaye-Blake et al [12] identified and assessed the resilience dimensions and thresholds in New Zealand with five dimensions, namely, social, economic, cultural, environmental, and institutional. Brown and Westaway [11] added the dimensions of Community Competence, Mobility, Information and Communication in addition to socio-economy in a study of agency, capacity, and resilience to environmental change: lessons from human development, well-being, and disasters.…”
Section: Dimension Of Community Resiliencementioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, Rela et al [1] tested the dimensions of community action; collective orderliness; and community, social and environmental adaptation. In the context of community resilience in rural areas, Payne et al [38] and William Kaye-Blake et al [12] identified and assessed the resilience dimensions and thresholds in New Zealand with five dimensions, namely, social, economic, cultural, environmental, and institutional. Brown and Westaway [11] added the dimensions of Community Competence, Mobility, Information and Communication in addition to socio-economy in a study of agency, capacity, and resilience to environmental change: lessons from human development, well-being, and disasters.…”
Section: Dimension Of Community Resiliencementioning
confidence: 99%
“…Then, Walton [67] divided these resources into five dimensions, namely: (1) strategic thinking (planning, visioning, leadership, positioning, learning, harnessing and using information, succession planning); (2) links within communities and bridging links to the community; (3) effective use of resources; (4) commitment and perseverance; and (5) trusting and respectful relationships (e.g., trust, openness, transparency, and mutual respect). Payne, et al [38] and William Kaye-Blake et al [12] identified and assessed the five dimensions of community resilience, namely, social, economy, culture, environment, and institutions, whereas Brown and Westaway [11] used social and cultural dimensions, economic development, community competence, mobility, information, and communication. The latest article from Rela et al [1] examined the dimensions of community action, collective orderliness, and community adaptation.…”
Section: Construction Of Model and Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…While much literature omits the definition of an indicator but focuses straight on its qualities, Kaye-Blake et al ( 26 ) define an indicator as a “relevant variable, measurable over time and/or space that provides information on a larger phenomenon of interest and allows comparisons to be made.” Hence, community indicators quantify different aspects of community characteristics over time. The implementation and integration of health promotion principles into the prevention and management of mental health problems depends upon a good understanding of the specific social and physical indicators regarding the individual and its (health) context ( 11 ).…”
Section: Introductionmentioning
confidence: 99%